The contested reform for the extension and strengthening of the judicial and prosecutorial careers - Rasillo López, Pilar (EUNOMÍA. Revista en Cultura de la Legalidad, 2025)
The article analyses the access systems for the judicial and prosecutorial careers regulated in the Draft Organic Law amending Organic Law 6/1985, of 1 July, on the Judiciary, and Law 50/1981, of 30 December, regulating the Organic Statute of the Public Prosecutor's Office, for the extension and strengthening of the judicial and prosecutorial careers. The article focuses on the purposes that justify the reform, concluding that the objectives pursued are not met.
Keywords: judicial and prosecutorial careers; reform; access systems